Implementation Of Enhanced Recovery After Surgery (Eras) Guidelines in Elective Cesarean Sections - Kalpana L, Kalpana L; Sharma, Nidhi (Journal of Neonatal Surgery, 2025)
Background: Enhanced Recovery After Surgery (ERAS) protocols are evidence-based, multidisciplinary strategies designed to improve postoperative outcomes. Their application in obstetrics, particularly elective cesarean sections (CS), is growing but remains underutilized despite evidence suggesting improved recovery and patient satisfaction. Methods: This single-center randomized controlled trial enrolled 120 women undergoing elective CS. Participants were randomized 1:1 into ERAS and standard care groups. The ERAS protocol emphasized early mobilization, multimodal analgesia, and early oral intake. The primary outcome was postoperative length of hospital stay. Secondary outcomes included pain scores (VAS), time to ambulation and feeding, complications, and satisfaction. Results: The ERAS group had significantly shorter hospital stays (mean: 48.2 vs. 72.6 hours; p<0.001), lower pain scores at all time points (p<0.001), earlier ambulation (6.5 vs. 12.8 hours; p<0.001), and earlier oral intake (2.2 vs. 8.4 hours; p<0.001). Complication rates were lower in the ERAS group (10% vs. 30%; p=0.008). Satisfaction scores were higher in pain management, mobility, and overall experience (p<0.001). Conclusion: ERAS protocols significantly enhance postoperative recovery, reduce complications, and improve patient satisfaction in elective CS without compromising safety. These findings support the wider adoption of ERAS in obstetric practice to optimize maternal outcomes and healthcare resource utilization.